2021
DOI: 10.3390/app11031150
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Auditory Augmented Reality Using a Position-Dynamic Binaural Synthesis System—Technical Components, Psychoacoustic Needs, and Perceptual Evaluation

Abstract: For a spatial audio reproduction in the context of augmented reality, a position-dynamic binaural synthesis system can be used to synthesize the ear signals for a moving listener. The goal is the fusion of the auditory perception of the virtual audio objects with the real listening environment. Such a system has several components, each of which help to enable a plausible auditory simulation. For each possible position of the listener in the room, a set of binaural room impulse responses (BRIRs) congruent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…One approach to this is by combining environmental IRs and HRTFs [139] when rendering virtual sounds. Alternatively, researchers can directly measure a user's binaural room impulse responses (BRIRs) in the environment of interest, which integrate room acoustics and the user's personal auditory perception [140,141] in one measurement. To avoid the complexity of in-situ measurements, it is also possible to simulate perceptually plausible BRIRs [142].…”
Section: Spatial Sound Synthesismentioning
confidence: 99%
“…One approach to this is by combining environmental IRs and HRTFs [139] when rendering virtual sounds. Alternatively, researchers can directly measure a user's binaural room impulse responses (BRIRs) in the environment of interest, which integrate room acoustics and the user's personal auditory perception [140,141] in one measurement. To avoid the complexity of in-situ measurements, it is also possible to simulate perceptually plausible BRIRs [142].…”
Section: Spatial Sound Synthesismentioning
confidence: 99%
“…Note that the scope of this chapter covers reverberation's spatial features from the listener's point of view, but not from the source's point of view. Therefore, sound source directivity is not discussed, even though it is an important topic on its own-e.g., it is essential to model it correctly in a six-degrees-of-freedom (6DoF) application where the listener is allowed to walk past a directional source [51].…”
Section: Simulating Reverberation Efficientlymentioning
confidence: 99%
“…Furthermore, a simple approximation can be employed by convolving HRTF corresponding to the direction of source relative to the listener with a fixed RIR for all positions in the same environment. Neidhardt et al indicated that the adaptation of only the direct sound with corresponding HRTFs could be used to create convincing virtual sound illusions [72].…”
Section: A Room Auralization Using Rendering Filtermentioning
confidence: 99%
“…Another important consideration in dynamic rendering is the position resolution for the BRIR update. Efficient dynamic rendering can be achieved by updating BRIRs based on the required minimum grid resolution of the user's positional changes [72]. The minimum grid resolution can be derived based on perceptual thresholds such as minimum audible angle for head rotations and the just noticeable differences of distance changes induced by the user's head/body translation.…”
Section: A Room Auralization Using Rendering Filtermentioning
confidence: 99%